2002
DOI: 10.1080/13550280290167902
|View full text |Cite
|
Sign up to set email alerts
|

The Protean Manifestations of Varicella-Zoster Virus Vasculopathy

Abstract: Varicella-zoster virus (VZV) vasculopathy in the central nervous system (CNS) affects large and small cerebral vessels. Large-vessel disease is most common in immunocompetent individuals, whereas small-vessel disease usually develops in immunocompromised patients. In some patients, both large and small vessels are involved. Neurological features are protean. Neurological disease often occurs months after zoster and sometimes without any history of zoster rash. Magnetic resonance imaging (MRI) scanning, cerebra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
55
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(58 citation statements)
references
References 21 publications
3
55
0
Order By: Relevance
“…As in adults, the CSF in children with VZV vasculopathy contains amplifiable VZV DNA or anti-VZV antibody, indicative of active infection (Table 1) and consistent with the detection of VZV antigen in granulomatous arteritis lesions of the left MCA of a 4-year-old girl who developed TIAs 8 months after varicella and died of malignant left hemispheric infarction 5 months later (15). Radiologically, PVA and VZV vasculopathy in childhood resemble the VZV vasculopathy described in immunocompromised patients and older adults (31), with large-vessel arteriopathy involving the anterior circulation reported most often in virologically-confirmed VZV vasculopathy in childhood (Table 1).…”
Section: Vzv Vasculopathy In Childrensupporting
confidence: 65%
“…As in adults, the CSF in children with VZV vasculopathy contains amplifiable VZV DNA or anti-VZV antibody, indicative of active infection (Table 1) and consistent with the detection of VZV antigen in granulomatous arteritis lesions of the left MCA of a 4-year-old girl who developed TIAs 8 months after varicella and died of malignant left hemispheric infarction 5 months later (15). Radiologically, PVA and VZV vasculopathy in childhood resemble the VZV vasculopathy described in immunocompromised patients and older adults (31), with large-vessel arteriopathy involving the anterior circulation reported most often in virologically-confirmed VZV vasculopathy in childhood (Table 1).…”
Section: Vzv Vasculopathy In Childrensupporting
confidence: 65%
“…Pathological studies have shown viral antigen and nucleic acid in the affected arteries. Encephalitis also results from a small-vessel vasculopathy that produces multiple infarcts in both cortical and subcortical gray and white matter combined with deep white matter ischemic or demyelinating lesions (8,93,95,96,129). Zoster infection in immunocompromised patients also may result in a necrotizing infection of ependymal cells resulting in ventriculitis and periventriculitis, usually presenting with hydrocephalus, altered mental status, and gait difficulty.…”
Section: Viruses For Which Pcr Has Potential Efficacy In Diagnosis Bumentioning
confidence: 99%
“…Only CSF negative for both VZV DNA and anti-VZV IgG antibody can reliably exclude the diagnosis of VZV vasculopathy [25]. On imaging, both cortical and deep-seated FLAIR hyperintensities can be seen; lesions at the gray-white matter junctions in particular, some of which enhance, provide strong supportive evidence to VZV as the cause of disease [27,28]. In the study by Nagel et al stated earlier, the prevalence of rash, CSF pleocytosis or vascular abnormalities on MRA/conventional angiography were seen in two thirds of the patients, while abnormalities on CT/MRI were seen in almost all patients with VZV vasculopathy [14].…”
Section: Investigationsmentioning
confidence: 92%